Long-Term Survival After Transhiatal Versus Transthoracic Esophagectomy: A Population-Based Nationwide Study in Finland - Junttila Anna; Helminen Olli; Helmiö Mika; Huhta Heikki; Kallio Raija; Koivukangas Vesa; Kokkola Arto; Laine Simo; Lietzen Elina; Meriläinen Sanna; Pohjanen Vesa-Matti; Rantanen Tuomo; et al. (Springer, 2025)
Background
No population-based studies comparing long-term survival after transhiatal esophagectomy (THE) and transthoracic esophagectomy (TTE) exist. This study aimed to compare the 5-year survival of esophageal cancer patients undergoing THE or TTE in a population-based nationwide setting.
Methods
This study included all curatively intended THE and TTE for esophageal cancer in Finland during 1987-2016, with follow-up evaluation until 31 December 2019. Cox proportional hazard models provided hazard ratios (HRs) with 95% confidence intervals (CIs) of 5-year and 90-day mortality. The results were adjusted for age, sex, year of operation, comorbidities, histology, neoadjuvant treatment, and pathologic stage.
Results
A total of 1338 patients underwent THE (n = 323) or TTE (n = 1015). The observed 5-year survival rate was 39.3% after THE and 45.0% after TTE (p = 0.072). In adjusted model 1, THE was not associated with greater 5-year mortality (HR 0.99; 95% CI 0.82-1.20) than TTE. In adjusted model 2, including T stage instead of pathologic stage, the 5-year mortality hazard rates after THE (HR 0.87, 95% CI 0.72-1.05) and TTE were comparable. The 90-day mortality rate for THE was higher than for TTE (adjusted HR 0.72; 95% CI 0.45-1.14). In subgroup analyses, no differences between THE and TTE were observed in Siewert II gastroesophageal junction cancers, esophageal cancers, or pN0 tumors, nor in the comparison of THE and TTE with two-field lymphadenectomy. The sensitivity analysis, including patients with missing patient records, who underwent surgery during 1996-2016 mirrored the main analysis.
Conclusions
This Finnish population-based nationwide study suggests no difference in 5-year or 90-day mortality after THE and TTE for esophageal cancer.